Phenolic derivatives from Garcinia multiflora Champion ex Bentham and their chemotaxonomic significance. (February 2020) - Yang, Haojie; Tian, Dongsong; Zeng, Yanrong; Huang, Liejun; Gu, Wei; Hao, Xiaojiang; Yuan, Chunmao
Abstract: A phytochemical investigation of the leaves and twigs of Garcinia multiflora Champion ex Bentham led to the isolation of eleven phenolic derivatives, including a new polycyclic polyprenylated acylphloroglucinol (PPAP, 1 ), five known PPAPs (2 –6 ), three xanthones (7 –9 ), a benzophenone (10 ), and a methyl phenyl acetate derivative (11 ). Their structures were established by extensive spectroscopic analysis, including HR-ESI-MS and NMR. Five compounds (1, 2, 4, 5, and 11 ) were first found in the genus Garcinia, of which compounds 1 and 11 were reported from the family Guttiferae for the first time. The chemotaxonomic significance of the isolated compounds was discussed. Furthermore, six PPAPs showed good cytotoxicities with IC50 values ranging from 1.79 to 9.40 μM. Graphical abstract: Image 1 Highlights: Eleven phenolic derivatives were isolated from Garcinia multiflora Champion ex Bentham (Guttiferae). Five compounds (1, 2, 4, 5, and 11 ) were reported from the genus Garcinia for the first time. The chemotaxonomic significance of the isolated compounds was discussed. Six compounds showed good cytotoxicities with IC50 values ranging from 1.79 to 9.40 μM.